Terrestrial insects as the main food for freshwater fish in Sungai Kerian tributaries: an implication on habitat conservation - Mohd Shafiq Zakeyuddin,; Mansor Mat Isa,; Che Salmah Md Rawi,; Amir Shah Ruddin Md Sah,; Abu Hassan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The importance of terrestrial insects as food items for freshwater fish was studied by examining stomach contents of Devario regina (Fowler 1934) and its population parameters at canopied areas of selected tributaries of Sungai Kerian, in the northern state of Peninsular Malaysia. Ninety six percent (121 out of 126) of the fish stomachs examined contained food materials in the stomachs and the values of percentage of occurrence (%F), percentage numerical (%N) and percentage points (%P) indicated that collected fish ate similar food items in all rivers. Among the food categories, scavenging terrestrial ants (Formicidae) were the most dominant food item, hence the main diet for this species. The Index of Relative Importance (IRI) scores of food items indicated that ants were higher than other food items. This surface water feeder experienced a positive allometric growth (W = aLb) with a b (rate of growth) value of 3.256. Its asymptotic length, growth constant and growth performance index represented this species with a short life-span (L∞ = 10.90 cm, K = 1.20 year-1, φ’ = 2.15, tmax = 3 year, respectively) and had higher natural mortality (M = 2.40 year-1) than fishing mortality (F = 0.35 year-1) while the fish stock was underexploited (E = 0.13). The finding of this study indicated the importance of terrestrial ants as a food source that support excellent growth of D. regina and the need to conserve riparian trees along river banks to provide allocthonous materials and habitats for the ants.